The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1088/1361-665x/ab80e4
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive elastic metastructures from magneto-active elastomers

Abstract: Elastic metastructures provide advanced control of elastic wave propagation, particularly through their ability to exhibit frequency band gaps where elastic waves cannot propagate. Several metastructure design strategies to realize band gaps in frequency ranges of interest have emerged in recent years. However, the band gap frequencies are fixed at design time by the metastructure geometry and constituent materials. Here, a tunable metamaterial is developed which utilizes the coupled magneto-mechanical respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…Other types of magnetically controlled mechanical metamaterials, which utilize field-induced stiffening to exhibit field-dependent structural properties or behaviors in response to applied static or dynamic mechanical loads, have been demonstrated. 164,326,327 Active metamaterials made of magnetic soft materials have demonstrated potential for applications in unconventional soft robotics, 157,163 acoustic metastructures with tunable bandgap, 325 and smart vibrationresistant structures. 327 6.1.3.…”
Section: Applications Of Magnetic Soft Materials and Robotsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other types of magnetically controlled mechanical metamaterials, which utilize field-induced stiffening to exhibit field-dependent structural properties or behaviors in response to applied static or dynamic mechanical loads, have been demonstrated. 164,326,327 Active metamaterials made of magnetic soft materials have demonstrated potential for applications in unconventional soft robotics, 157,163 acoustic metastructures with tunable bandgap, 325 and smart vibrationresistant structures. 327 6.1.3.…”
Section: Applications Of Magnetic Soft Materials and Robotsmentioning
confidence: 99%
“…164,326,327 Active metamaterials made of magnetic soft materials have demonstrated potential for applications in unconventional soft robotics, 157,163 acoustic metastructures with tunable bandgap, 325 and smart vibrationresistant structures. 327 6.1.3. Programmable and Reconfigurable Surfaces.…”
Section: Applications Of Magnetic Soft Materials and Robotsmentioning
confidence: 99%
“…The current work is a just preliminary investigation on utilizing surface wrinkles to tune wave propagations. It has been shown that magnetic actuation can also serve as a desirable way to alter material properties or to induce finite deformation such that wave propagations can be controlled [67][68][69][70][71][72]. Consequently, other contactless loading approach as well as the dynamical behaviors of liquid crystal elastomers will be investigated in the future based on some reduced models [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the use of a rotating magnetic field transforms the particle distribution to a plane-like microstructure [31]. Recently, anisotropic MAEs are also synthesized using novel 3D-printing techniques [32][33][34]. The mechanical properties of MAEs are highly sensitive to the initial shape of a sample [35][36][37][38] as well as to the particle microstructure [39][40][41].…”
Section: Introductionmentioning
confidence: 99%